Typification of Candollean names in the tribe Gnaphalieae (Asteraceae) - Remya, S.; Maya, C.N. (Rheedea, 2026)
Revisionary studies on the tribe Gnaphalieae of Asteraceae (subfam. Asteroideae) in southern India could identify many names attached to different collections at various herbaria, without precise original materials designated as types. Candollean names of Anaphalis notoniana DC., Helichrysum buddleioides DC., and Pseudognaphalium hypoleucum (DC.) Hilliard & B.L.Burtt, have been typified following the latest botanical code.